2021
DOI: 10.3389/fimmu.2021.602717
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Different Extracellular Vesicles in the Hydatid Fluid of Echinococcus granulosus and Immunomodulatory Effects of 110 K EVs on Sheep PBMCs

Abstract: Echinococcosis, mainly caused by Echinococcus granulosus, is one of the 17 neglected tropical diseases. Extracellular vesicles (EVs) play an essential role in the host–parasite interplay. However, the EVs in the hydatid fluid (HF) of E. granulosus are not fully characterized. Herein, three different types of HF EVs, designated as 2 K, 10 K, and 110 K EVs based on the centrifugal force used, were morphologically identified. A total of 97, 80, and 581 proteins were identified in 2 K, 10 K, and 110 K EVs, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
(81 reference statements)
3
16
0
Order By: Relevance
“…The dimensions of exosome-like vesicles obtained from F. hepatica ranged from 37 to 153 nm [ 37 ]. In Schistosoma mansoni , the comparable values were 50–130 nm [ 38 ]; in O. viverrini , 40–180 nm [ 15 ]; in Nippostrongylus brasiliensis , 60–160 nm [ 39 ]; in Trichuris muris 30–150 nm [ 40 ]; in Brugia malayi , 85–200 nm [ 41 ]; in Ascaris suum , 80–200 nm [ 42 ] and in E. granulosus , 50– 350 nm [ 43 ]. NTA analysis showed that F. hepatica 120k EVs and F. gigantica 110k EVs are smaller than the 100k EVs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions of exosome-like vesicles obtained from F. hepatica ranged from 37 to 153 nm [ 37 ]. In Schistosoma mansoni , the comparable values were 50–130 nm [ 38 ]; in O. viverrini , 40–180 nm [ 15 ]; in Nippostrongylus brasiliensis , 60–160 nm [ 39 ]; in Trichuris muris 30–150 nm [ 40 ]; in Brugia malayi , 85–200 nm [ 41 ]; in Ascaris suum , 80–200 nm [ 42 ] and in E. granulosus , 50– 350 nm [ 43 ]. NTA analysis showed that F. hepatica 120k EVs and F. gigantica 110k EVs are smaller than the 100k EVs [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reports on EVs of cestodes are currently limited to Taenia asiatica [ 41 ], Taenia saginata and Echinococcus [ 19 ], and they mainly focused on interactions between EVs of cyst fluid and immune cells such as macrophages and dendritic cells [ 42 , 43 ]. Yang [ 44 ] found one type of 110-KDa EVs in the HF of E. granulosus containing 25 miRNAs, which were internalised by sheep peripheral blood mononuclear cells in a time-dependent manner to upregulate IL-10, TNF-α and IRF5, and downregulate IL-1β, IL-17 and CD14. Exosome-related miRNAs contribute to the interaction between host and parasites in worms [ 45 ] and affect host immune response [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reports on EVs of cestodes are currently limited to Taenia asiatica [45], Taenia saginata and Echinococcus [19](Ancarola et al, 2017), and mainly focusing on interactions between EVs of cyst uid and immune cells such as macrophages and dendritic cells [46][47]. Yang J [48] found one type of 110 K EVs from hydatid uid (HF) of E. granulosus, which loaded 25miRNAs, were internalized by sheep peripheral blood mononuclear cells (PBMCs) in a time-dependent manner and thus induced interleukin (IL)-10, tumor necrosis factor-α (TNF-α), and IRF5 were signi cantly upregulated and IL-1β, IL-17, and CD14 were signi cantly downregulated. Exosome-related miRNAs contributes to the interaction between host and parasites in worms [49] and affects host immune response [50], However, there were few reports on the regulation mechanism of EVs-related miRNAs on the development of parasite.…”
Section: Discussionmentioning
confidence: 99%